The origins of journalism education at UPNG - Peter Henshall (Asia Pacific Network, 1997)
Journalism education training was started at the University of PNG at the beginning of 1975, when the New Zealand Government agreed to fund a one-year Diploma in Journalism for an initial two-year period. Before this, the few national journalists employed in Papua New Guinea had been trained in-house by the two-principal employers of the time— the Office of Information and the National Broadcasting Commission.